2022
DOI: 10.3389/frobt.2022.886074
|View full text |Cite
|
Sign up to set email alerts
|

Mastication-Enhanced Taste-Based Classification of Multi-Ingredient Dishes for Robotic Cooking

Abstract: Chefs frequently rely on their taste to assess the content and flavor of dishes during cooking. While tasting the food, the mastication process also provides continuous feedback by exposing the taste receptors to food at various stages of chewing. Since different ingredients of the dish undergo specific changes during chewing, the mastication helps to understand the food content. The current methods of electronic tasting, on the contrary, always use a single taste snapshot of a homogenized sample. We propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…PC1 accounted for the most variation in impedance values (76.4%), while PC2 accounted for the next largest variation (23.6%). Other classification algorithm such as K-nearest neighbors, decision trees, and support vector machines were also effective in carrying out such tasks [ 39 ]. The distances of samples in sucrose subsets were closer due to the larger molecular volume, which were difficult to adsorb and desorb under the AC current disturbance of EIS.…”
Section: Resultsmentioning
confidence: 99%
“…PC1 accounted for the most variation in impedance values (76.4%), while PC2 accounted for the next largest variation (23.6%). Other classification algorithm such as K-nearest neighbors, decision trees, and support vector machines were also effective in carrying out such tasks [ 39 ]. The distances of samples in sucrose subsets were closer due to the larger molecular volume, which were difficult to adsorb and desorb under the AC current disturbance of EIS.…”
Section: Resultsmentioning
confidence: 99%
“…It was also theorized that human taste can be reproduced using a learning robot that produces its energy from organic matter using microbial fuel cells (MFCs) (Sochacki, Abdulali, Cheke, et al, 2023). As the MFC has chemical requirements as comes to its feed, the robot can learn what it likes depending on the current output of the cell.…”
Section: From Sensing To Tastingmentioning
confidence: 99%
“…Robotic taste is a recent development [4], [45], and has so far been used to cook dishes catering to specific human preferences. In this case, we choose a combination of sensors that can sense the substances needed by the fuel cell.…”
Section: Taste Sensingmentioning
confidence: 99%
“…There was a successful attempt to build a robot that hunted slugs [49]. Moreover, it was shown that mastication can improve taste sensing for robots [45]. Given the scarcity of data, we do not attempt a complicated feeding mechanism for our hypothetical robot but will use liquid feeds only.…”
Section: Feeding Mechanismmentioning
confidence: 99%